Surgical treatment of giant phyllodes tumors of the breast: a series of rare cases - Chen, Chang; Xu, Ying; Huang, Xin; Lin, Yan; Sun, Qiang (Frontiers in Oncology, 2025)
BackgroundPhyllodes tumors (PTs) are rare interstitial tumors that account for <1% of all breast tumors. The best surgical option for PTs is controversial, particularly in patients with giant PTs.MethodsThis retrospective single-center study selected patients with giant borderline/malignant PT (>10 cm) treated in our center between January 2017 and July 2022. We conducted a detailed analysis and identified rare cases. Survival analysis was performed using the Kaplan–Meier method.ResultsThis study included 24 patients with PTs >10 cm, including 15 borderline and nine malignant PTs. Among these patients, 12 underwent extended lumpectomy and 12 underwent mastectomy at initial diagnosis. All patients were followed up for a median of 49.8 months. Local recurrence occurred in 50% of the patients who underwent lumpectomy, whereas none of the patients who underwent mastectomy and achieved R0 resection had recurrence. Several special cases are described in detail separately.ConclusionMastectomy may reduce local recurrence rates in patients with giant borderline/malignant PTs of the breast. Complete tumor resection and clean margins are the most important factors in controlling local recurrence.